PLANT-DOMINANT LOW PROTEIN (PLADO) DIET UNTUK MANAJEMEN KONSERVATIF PENYAKIT GINJAL KRONIK (PGK) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Chronic Kidney Disease in the world is currently increasing and becoming a serious health problem. In 2017, there were 697.5 million cases of CKD at all stages of development, with a recorded global prevalence of 9.1 percent. The prevalence of CKD in Indonesia has increased from 2 percent (Riskesdas 2013) to 3.8 percent (Riskesdas 2018). New patients and active patients undergoing hemodialysis are increasing, with high costs and associated functional disorders, reduced health-related quality of life, and high mortality rates. The most recent declaration of World Kidney Day implements strategies that reduce the burden of kidney failure by slowing the progression of CKD and controlling uremia without dialysis. Dietary interventions have a role in improving CKD outcomes and preventing or delaying dialysis initiation. Evidence suggests that a patient-centered (PLADO) predominantly plant-based low-protein diet, with an amount of 0.6–0.8 g/kg/day consisting of >50 percent plant sources for CKD non-dialysis showed good results. The scientific premise of PLADO stems from the observation that a high-protein diet with a high meat intake results not only in a higher risk of cardiovascular disease but also a higher incidence of CKD and more rapid development of CKD due to increased intraglomerular pressure and glomerular hyperfiltration. Meat intake increases production of nitrogenous end products, exacerbates uremia, and may increase the risk of constipation with hyperkalemia resulting from low fiber intake. A plant-dominated, fiber-rich, low-protein diet can induce beneficial changes in the gut microbiome, which can modulate uremic toxin formation and slow the progression of CKD, as well as reduce cardiovascular risk. PLADO is a healthy, safe, flexible, and feasible diet that can form the core of a conservative CKD management strategy.